“Sobrecarga del cuidador y la relación de pareja en padres de los usuarios de la asociación de familiares de personas excepcionales de Chimborazo periodo diciembre 2016-mayo 2017” - Barahona Barrera, Stephany Elizabeth (2017)
This researching was performed in Chimborazo Association of Exceptional People Relatives, during December 2016 to May 2017, its main objective was to analyze the overloading of caregiver and couple relation between parents’ users, was worked with a population of 40 parents and with a no probabilistic sample of 20 direct caregivers of cerebral palsy people applying inclusion and exclusion criteria. It was used the scientific method, design was transversal, type of researching was field and bibliographical research and the level of researching is descriptive. The techniques and instruments of data collection which was used were: Zarit scale for assessing caregiver burden to determine the levels of overloading by caregiver and the Survey to evaluate the couple relation which was designed by researching authors, due to lack of scales that measure the quality of couple relation. After doing tabulation and analysis data was gotten the following outcomes: Zarit scale for assessing caregiver burden: It can identify that the most of parents show overloading since 15% of population manifest light overloading and 40% show intense overloading, which represents a total of 55% of evaluated population, on the other hand 45% of population don’t show any type of overloading. The outcomes of Survey to evaluate the couple relation were: 15.5 % of population delay influencing in their quality of couple relation, 16.5% of people show that the most of times the quality of their couple relation has been influenced, 32.5% mention that sometimes the quality of couple relation has seen influenced, and 35.5% demonstrate that quality of their couple relation never has been influenced so that is gotten to identify that 64.5% of population has had troubles into couple relation. In conclusion is gotten to determine that the most direct caregiver parents of cerebral palsy people show overloading (55%) and through the survey was determined that exists influencing in quality of couple relation (64.5%).